FACTOR AFFECTING THE EFFECTIVENESS OF INTERNAL AUDIT IN BANK IN INDONESIA (Study Case Bank in DKI Jakarta) - Clara Augustine; Anis Chariri (Diponegoro Journal of Accounting, 2025)
This study investigates the factors that influence the effectiveness of internal audits in the Indonesian banking sector, particularly in the DKI Jakarta region, using Attribution Theory as its theoretical foundation. The study empirically examines the influence of internal auditor competence, internal auditor independence, management support, and organizational culture on the effectiveness of internal audits. Using a quantitative approach, data were collected through structured questionnaires from 105 internal auditors and related staff at Indonesian commercial banks and were analyzed using multiple linear regression.The research findings indicate that internal auditor competence, internal auditor independence, and organizational culture have a significant positive influence on the effectiveness of internal audits. These results underscore that the professional capabilities of auditors, their autonomy from intervention, and a transparent and ethical organizational culture are crucial for the success of internal audits in the banking industry. However, the hypothesis regarding management support was rejected, as no statistically significant influence on internal audit effectiveness was found within the context of this study.Theoretically, this study contributes by applying Attribution Theory to explain how the perception of audit effectiveness is shaped by attributions to stable, internal factors like competence and culture. Practically, the findings offer insights for banking management and regulators to focus on enhancing auditor competence, strengthening independence, and developing an organizational culture that supports accountability to improve audit quality, mitigate fraud risks, and reinforce governance frameworks in the Indonesian financial sector